Airway function in infancy is linked to airflow measurements and respiratory symptoms from childhood into adulthood - Owens, L.; Laing, I.; Zhang, Guicheng; Turner, S.; Le Souëf, P. (Wiley-Liss, Inc, 2018)
© 2018 Wiley Periodicals, Inc. Introduction: Increasing evidence suggests that poor lung function in adulthood is determined very early in life. Our study aims were: (1) identify factors associated with early infant lung function; (2) quantify the link between early infant lung function and early adult lung function; and (3) identify environmental and inherited factors which predict lung function throughout the post-natal growth period. Methods: In this longitudinal study, 253 individuals were recruited antenatally. Lung function and allergy testing occurred at 1, 6, 12 months, 6, 11, 18, and 24 years of age. The relationship between lung function at 1 month (V'maxFRC) and spirometry variables at each follow-up was evaluated. Early life predictors of spirometry were assessed longitudinally using linear mixed models. Results: V'maxFRC correlated positively with FEF25-75% at every assessment from 6 to 24 years and FEV 1 /FVC at 11 and 24 years and inversely with airway responsiveness at 6 and 18 years. Maternal asthma and smoking in pregnancy were associated with lower FEV 1 from 6 to 24 years (-99mL, P=0.03; -77mL, P=0.045 respectively). Lower V'maxFRC at 1 month was associated with asthma and wheeze through to 24 years. Conclusion: Lung airflow measurements track from birth into early adulthood, suggesting a permanent and stable airway framework is laid down in the antenatal period. Lower infant airway function is associated with respiratory symptoms into adulthood, indicating the link is clinically important. Antenatal and early life exposures must be addressed in order to maximize airway growth and reduce lifelong respiratory compromise.